New burial rites at the end of the Linearbandkeramik in south-west Slovakia. (February 2021) - Müller-Scheeßel, Nils; Hukeľová, Zuzana; Meadows, John; Cheben, Ivan; Müller, Johannes; Furholt, Martin
Abstract: Abstract : The recent discovery of several late Linearbandkeramik (LBK) sites in Central Europe, including Vráble in south-west Slovakia, has revealed evidence for increasing diversity in Neolithic mortuary practices, which may reflect inter-community war and socio-political crisis at the end of the LBK. Here, the authors combine osteological and radiocarbon analyses of inhumations from Vráble. Rather than a straightforward sign of inter-community conflict and war, this development reflects a culmination of internal conflict and a diversification in the ritual treatment of human bodies. The emerging variability in LBK methods of manipulating and depositing dead bodies can be interpreted as an experimental approach in how to negotiate social conflicts and community boundaries.